Sistem Informasi Monitoring Barang Berbasis Web di CV. Rekam Media Indonesia - Afif Lukman; Nugroho Eko Budiyanto (Universitas Wahid Hasyim, 2023)
CV. Rekam Media Indonesia is a company engaged in the field of photography and videography equipment rental services. The problem that occurs in the current system is that for the processing of adding daily rental data, adding rental equipment and sales of goods that are old enough to collect data manually and separately, so that the process of doing so takes quite a long time and difficulties in do time efficiency. The purpose of this research is to create a WEB-based goods monitoring information system that will be used at the Rekam Media Indonesia office. The development method used in this research is the Waterfall Method and the information system that has been produced will later be able to manage daily incoming and outgoing camera rental records, then purchase data for tools as well as sales of rental equipment on one web platform so that it makes work easier and easier. can develop on other matters related to promotion or production.